2013
DOI: 10.1007/jhep11(2013)078
|View full text |Cite
|
Sign up to set email alerts
|

Degenerating Black Saturns

Abstract: Abstract:We investigate the possibility of constructing degenerate Black Saturns in the family of solutions of Elvang-Figueras. We demonstrate that such solutions suffer from naked singularities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Except for the Myers-Perry [1] and the doubly-spinning black ring solution [4], each black hole horizon of all the known exact solutions in D = 5 mentioned above only has one nonvanishing angular momentum. In-depth studies of the black saturn solution [6,30], concentric black ring solution (di-rings) [7,8] and orthogonal black ring solution (bi-rings) [9,10] have shown that they do not exhibit regular extremal limits, or extremal limits that do not involve naked singularities. The only known solutions that admit regular extremal limits are the Myers-Perry and the doubly-spinning black ring solution.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the Myers-Perry [1] and the doubly-spinning black ring solution [4], each black hole horizon of all the known exact solutions in D = 5 mentioned above only has one nonvanishing angular momentum. In-depth studies of the black saturn solution [6,30], concentric black ring solution (di-rings) [7,8] and orthogonal black ring solution (bi-rings) [9,10] have shown that they do not exhibit regular extremal limits, or extremal limits that do not involve naked singularities. The only known solutions that admit regular extremal limits are the Myers-Perry and the doubly-spinning black ring solution.…”
Section: Introductionmentioning
confidence: 99%